2013
DOI: 10.1038/mi.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental role for HIF-1α in constitutive expression of human β defensin-1

Abstract: Antimicrobial peptides are secreted by the intestinal epithelium to defend from microbial threats. The role of human β defensin-1 (hBD-1) is notable because its gene (DEFB1) is constitutively expressed and its antimicrobial activity is potentiated in the low-oxygen environment that characterizes the intestinal mucosa. Hypoxia-inducible factor (HIF) is stabilized even in healthy intestinal mucosa and we identified that epithelial HIF-1α maintains expression of murine defensins. Extension to a human model reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 39 publications
(47 reference statements)
2
111
1
5
Order By: Relevance
“…Human β defensin-1 (hBD1) is notable within the intestinal epithelium because it is constitutively secreted, whereas other antimicrobial peptides are induced by inflammatory mediators (8). Constitutive expression of hBD1 depended on basal HIF-1α signaling in multiple IEC lines and hBD1 expression correlated with other HIF target genes in human tissues (12). Another distinguishing feature of hBD1 is that the full spectrum of its antimicrobial activity is only revealed when its disulfide bonds are reduced (57).…”
Section: Molecular Aspects Of Barrier Regulation In the Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…Human β defensin-1 (hBD1) is notable within the intestinal epithelium because it is constitutively secreted, whereas other antimicrobial peptides are induced by inflammatory mediators (8). Constitutive expression of hBD1 depended on basal HIF-1α signaling in multiple IEC lines and hBD1 expression correlated with other HIF target genes in human tissues (12). Another distinguishing feature of hBD1 is that the full spectrum of its antimicrobial activity is only revealed when its disulfide bonds are reduced (57).…”
Section: Molecular Aspects Of Barrier Regulation In the Mucosamentioning
confidence: 99%
“…First, in the normal GI mucosa, particularly in the colon, physiologic hypoxia predominates (7). These studies have shown that these low pO 2 conditions are critical for the constitutive expression of some innate immune factors (12) and certain epithelial tight junction proteins (13) (discussed below). Second, inflammatory lesions observed in models of colitis are profoundly hypoxic (or even anoxic), with pO 2 levels that are comparable to the pO 2 levels observed in some large tumors (7).…”
Section: Oxygen Utilization In the Mucosamentioning
confidence: 99%
“…21 HIF-1a regulates basal defensin expression in intestinal epithelial cells and is protective in murine experimental colitis. 22,23 The epithelial surfaces of the respiratory tract are continuously exposed to microbes. Innate and adaptive immune functions of diverse cell types such as resident alveolar macrophages, epithelial cells and dendritic cells are required to prevent and control infections of the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia has been reported to increase ITF and HBD expression in intestinal epithelial cells in previous studies; Furuta interpreted this process as the mechanism for maintenance of barrier function when oxygen levels are low 30,31 . Xu et al, demonstrated that ITF expression in the intestines of rats exposed to intrauterine asphyxia increased 72 h after birth 32 , followed by rapid proliferation of the mucosa with the recovery of intestinal function.…”
Section: Discussionmentioning
confidence: 99%